Antidepressant drug treatment modifies the neural processing of nonconscious threat cues. - Harmer, C; Mackay, C; Reid, C; Cowen, P; Goodwin, G (2006)
BACKGROUND: The amygdala is believed to play a key role in processing emotionally salient, threat-relevant, events that require further online processing by cortical regions. Emotional disorders such as depression and anxiety have been associated with hyperactivity of the amygdala, but it is unknown whether antidepressant treatment directly affects amygdala responses to emotionally significant information. METHODS: The current study assessed the effects of 7 days administration of the selective serotonin reuptake inhibitor (SSRI), citalopram, on amygdala responses to masked presentations of fearful and happy facial expressions in never-depressed volunteers using blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging. A double-blind, between-groups design was used with volunteers randomized to 20 mg/day citalopram versus placebo. RESULTS: Volunteers receiving citalopram showed decreased amygdala responses to masked presentations of threat compared with those receiving placebo. Citalopram also reduced responses within the hippocampus and medial prefrontal cortex (mPFC) specifically during the fear-relevant stimuli. These neural differences were accompanied by decreased recognition of fearful facial expressions assessed after the scan. By contrast, there was no effect of citalopram on the neural or behavioral response to the happy facial expressions. CONCLUSIONS: These results suggest a direct effect of serotonin potentiation on amygdala response to threat-relevant stimuli in humans. Such effects may be important in the therapeutic actions of antidepressants in depression and anxiety.